A Randomized Controlled Trial Comparing Behavioral, Educational, and Pharmacological Treatments in Youths With Chronic Tic Disorder or Tourette Syndrome - Rizzo, Renata; Pellico, Alessandra; Silvestri, Paola Rosaria; Chiarotti, Flavia; Cardona, Francesco (Frontiers in Psychiatry, 2018)
Context: The existing literature on the treatment of pediatric Chronic Tic Disorder (CTD) and Tourette Syndrome (TS) indicates that both Behavioral Therapy (BT) and Pharmaco-Therapy (PT) are effective for reducing symptoms. Objective: to evaluate the efficacy of BT compared to Psycho-Education (PE) or PT for reducing tics and co-occurring symptoms and for improving Quality of Life (QoL) in a sample of youths with CTD and TS. Design: a 10-weeks, 2 sites (Catania, Rome) randomized controlled trial. Participants were randomized to receive one of the following treatments: BT, PE or PT. Participants: 110 outpatients aged between 8-17 years affected by CTD or TS. Results: Patients in the BT and PT groups showed a significant reduction in the severity of tic symptoms, while the PE group did not show any improvement. PT was more effective for reducing obsessive compulsive symptoms than BT, while PE group did not show any improvement. Both BT and PT groups showed an improvement in most QoL domains, whereas no differences were found in the PE group. Conclusions: Behavioral Therapy is as effective as Pharmacological Therapy in the treatment of tic disorders in children and adolescents, thus offering an alternative to medications for CTD and TS.